Overview On Substance Induced Mood Disorders: Life Sciences-Substance Induced Mood Disorders - Mohammad Alsudairy, Najlaa; Abdullah Almuqrin, Ibrahim; Ali Shukr, Abdulrahman; Manajaa Alotaibi, Manal; Ahmed Hassan Alghamdi, Asma; Ibrahim Abbas, Wajdi; Hussam Abdullah A, Joraid; Abdullah Tban M, Alanazi; Mohammedhussain , Abdullah; Mohammed A Abu Murad, Dimah; Salem Mohammed S, Al Sharyah; Abdullah Aldalaan , Turki (International Journal of Life Science and Pharma Research, 2022)
Despite the fact that both illegal drugs and iatrogenic pharmaceuticals are taken with the intention of improving mood, a sizeable percentage of patients actually have paradoxical affective problems as a result of taking those prescriptions. Some people have manic or depressive episodes instead of the banal bliss that comes with drinking or the "hangover" the next day. Substanceinduced mood disorders are those that only manifest in conjunction with substance use. Bipolar disorder and its related disorders, as well as depressive disorders, are examples of affective disorders that can develop in the context of substance use. Previously, these diseases may be found in the DSM-nosological IV’s category of substance-induced mood disorders. However, "substanceinduced" is now a qualifier for mood disorders in the most recent DSM. In the general population, substance use disorders (SUDs) and depression and bipolar illness usually co-occur. The aim of this review is discussing substance-induced depressive disorder, substance-induced bipolar disorder, and related diseases. It will also go into further detail on how to tell them apart from mood disorders that co-occur with SUDs. Although it is no longer a separate category in the DSM-V, the term "substance-induced mood disorders" will be used to refer to both substance-induced depression and bipolar disorders for the purposes of this review. And the main objective is to collect research and review articles using trusted data base.